The economic effects of poor and fluctuating irrigation water salinity levels in the lower Vaal and Riet Rivers - Armour, Robert Jack (University of the Free State, 2002)
In the Lower Vaal and Riet Rivers, changing irrigation water quality has raised concern about the long-term sustainability of irrigation due to reduced yields of certain crops and the withdrawal of some very profitable crops. The main aim of this study is to develop and apply models to determine the long-term financial and economic viability of irrigation farming in the Lower Vaal and Riet Rivers, with specific aims to: evaluate the relationship between changing water quality, soil conditions and crop production; determine the impact on yield, crop choice, agronomic and water management practises, expected income and costs; develop models for typical farms in different river reaches, and apply these models to test the outcome of alternative scenarios regarding internal water quality management practises and external policy measures. Five case study farmers were selected, one from each of the different sub-areas of the OVIB study area. The case study farmers were representative of their sub-areas with regards to the hectares of irrigation water rights held, and jointly, also sufficiently representative of the OVIB region. With the contradicting aims of improved water use efficiency and increased leaching for salinity management, the importance of a financial optimisation model was evident to solve the apparent paradox between saving water due to it’s scarcity value and “wasting” water to leach out salts that build up in soils through the process of irrigation. SALMOD was constructed using GAMS and consists of a simulation and optimisation section that calculate the optimal crop enterprise, management and resource use combination that maximises farm returns under different water quality, management and policy scenarios. The management options built into SALMOD are the appropriate leaching fraction to implement and crop yield to accept for the optimal crop / resource combination calculated. The fixed capital management options included in SALMOD are the installation of artificial drainage, the change of irrigation system and the building of on-farm storage / evaporation dams for return-flow management. The % reduction in TGMASC from the long-term average ECiw (74 mS/m) to the worst expected Vaal River ECiw as predicted by Du Preez et al, (2000) for 2020 (159 mS/m), is 84% and 58% for the small farmers from Bucklands and Atherton respectively, between 13% and 16% for the Olierivier farmer, depending on whether the Vaal River of the Riet River has the major impact, 1% for the large and financially strong Vaallus farmer and 3% for the small yet resource strong New Bucklands farmer (see Table 5.38). These results clearly show that the small and resource poor farmers will be the most affected by irrigation water salinity deterioration. Scenario results from SALMOD further show that: - Leaching is financially viable for all case study farmers - Accepting lower yields on soils with insufficient leaching capacity is also financially viable - For farmers with limited area of well drained soils it can be financially viable to install artificial drainage - The option of building on-farm storage dams when returnflows are constrained to 100 mm per hectare water rights held, is financially infeasible for all case-study farms and for all scenarios - It is not financially viable for farmers to replace their current irrigation systems with more efficient water saving systems, but in some instances to replace them with systems that can apply a greater leaching fraction - At the worst-case scenario salinity conditions, farmers with below 60 ha water rights, and who don’t grow cotton, will go out of production. SALMOD has proved to be a valuable farm level salinity management tool. SALMOD is also potentially useful at regional and national level for determining the farm level financial impacts of various water quality and quantity scenarios where the farmers are affected by irrigation water salinity.

In die Benede Vaal- en Rietriviere het veranderende besproeiingswaterkwaliteit bekommernis veroorsaak oor die langtermyn volhoubaarheid van besproeiing weens verlaagde opbrengste van sekere gewasse asook die staking van verbouing van baie winsgewende gewasse. Die hoofdoel van die studie is om modelle te ontwerp en toe te pas om die langtermyn finansiële en ekonomiese volhoubaarheid van besproeiingslandbou in die Benede Vaal- en Rietriviere te bepaal, met verdere spesifieke doelwitte om: die verhoudinge te bepaal tussen veranderende waterversouting, grondomstandighede en gewasproduksie; die impak te bepaal op opbrengs, gewaskeuses, agronomiese en waterbestuurspraktyke en verwagte inkomste en uitgawes; modelle te ontwikkel vir tipiese plase in die verskillende riviertrajekte, en om die modelle toe te pas om die uitkomste te toets van alternatiwe scenarios van toepassing op interne waterkwaliteitsbestuurspraktyke en eskterne beleidsmaatreëls. Vyf gevallestudie boerderye was geselekteer, een vir elk van die verskillende sub-gebiede van die Oranje-Vaal Besproeingsraad (OVIB) gebied. Die gevallestudieboerderye is verteenwoordigend van die sub-gebiede met betrekking tot die hektare besproeiingswaterregte toegeken, en gesamentlik ook voldoende verteenwoodigend van die OVIB ondersoekgebied. Met die teenstrydige doelwitte van verhoogde waterverbruiksdoeltreffendheid en toenemende belangrikheid van loging vir vesoutingsbestuur, is die belangrikheid van ‘n finansiële optimaliseringsmodel duidelik, naamlik om die paradoks tussen waterbesparing weens die skaarsheidwaarde daarvan en watervermorsing om die soute wat deur die proses van besproeiing in die grond opgebou het, op te los en uit te loog. SALMOD is in GAMS opgestel en bestaan uit ‘n simulasie- en optimaliseringsafdeling wat die optimale gewasamestelling, bestuurs en hulpbron verbruikskombinasies bepaal wat plaasinkomstes maksimaliseer onder verskillende water kwaliteit , bestuurs- en beleidscenarios. Die bestuurskeuse wat in SALMOD ingebou is, is om die toepaslikste logingsfraksie te gebruik, en verlaagde gewasopbrengs te aanvaar om die optimale gewas- / hulpbronsamestelling te bepaal. Die vaste kapitaal bestuurskeuses wat in SALMOD ingebou is, is die installering van kunsmatige dreinering, die verandering van besproeiingstelsels en die bou van ‘n plaas opgaar / verdampingsdam vir terugvloeibestuur. Die persentasie afname in totale bruto marge bo gespesifiseerde kostes (TGMASC) vanaf die langtermyn gemiddelde elektriese geleiding van die besproeiingswater (ECiw = 74 mS/m) na die slegste verwagte Vaal Rivier ECiw soos beraam deur Du Preez et al, (2000) vir 2020 (159 mS/m), is 84% en 58% vir die klein boerderye van Bucklands en Atherton, tussen 13% en 16% vir die Olierivierboerdery, afhangende van of die Vaalrivier of die Rietrivier die hoof impak het, 1% vir die groot en finansieel sterk Vaallusboerdery en 3% vir die klein maar hulpbron-sterk New Bucklandsboerdery (sien Table 5.38). Die resultate wys duidelik dat die klein en hulpbronarm boerderye die meeste geaffekteer word deur besproeiingswaterversouting. Scenario resultate van SALMOD wys verder dat: - Loging finansieel uitvoerbaar is vir al die gevallestudieboerderye - Die aanvaarding van ‘n verlaagde opbrengs op gronde met onvoldoende logingskapasiteit ook finansieel uitvoerbaar is - Vir boerderye met onvoldoende goed gedreineerde gronde kan dit finansieel lonend wees om kunsmatige dreinering te installeer - Die opsie om ‘n opgaardam op die plaas te bou as besproeiingsterugvloei watervolumes tot 100 mm per hektaar waterregte toegeken, beperk is, is finansieel nie lonend vir al die gevallestudieboerderye en vir alle scenarios nie - Dit is nie finansieel uitvoerbaar vir boerderye om hulle huidige besproeiingsstelsels met ‘n meer doetreffende waterbesparingsstelsel te vervang nie, maar wel in sommige gevalle met ‘n stelsel wat ‘n groter logingsfraksie kan toedien - Vir die slegste geval versoutingscenario-omstandighede, sal boerderye met minder as 60 ha waterregte toegeken, en wat nie katoen kan plant nie, uit produksie gaan. SALMOD is ‘n nuttige plaasvlak versoutingsbestuurhulpmiddel. Ook is dit potensieel waardevol op gebieds- en nasionale vlak vir die bepaling van plaasvlak finansiële impakte van verskillende water kwaliteit and kwantiteit scenarios waar boerderye geaffekteer word deur besproeiingswatervesouting.
Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 2002
Keywords: Water salinization -- South Africa -- Costs; Irrigation farming -- Economic aspects -- South Africa; Linear programming optimisation; Farm level model; SALMOD; Farm level management options; Policy Guidelines; Lower Vaal and Riet Rivers; Economic impact; Irrigation agriculture; Irrigation water salinity; Soil salinisation